Genetic evaluation of Black Bengal Goat for reproductive traits - Desha, N H; Jalil, M A; Asha, A A A; Bhuiyan, A K F H; Amin, M R (Bangladesh Journal of Livestock Research, 2022)
This study aimed to evaluate the reproductive potentiality of Black Bengal goat. A total of 100 Black Bengal does were evaluated based on the recorded data that has been maintained under Black Bengal goat improvement program at Bangladesh Livestock Research Institute (BLRI), Savar, Dhaka. Investigation was done to ascertain the effect of generation, parity and season of birth of doe on birth weight (Bwt), age at first service (AFS), age at first kidding (AFK), average kidding interval (AKI) and average litter size per doe (ALS/doe).The mean Bwt, AFS, AFK, AKI and ALS/doe were 1.22±0.02 kg, 212.95±1.87 day, 360.26±1.88 day, 230.46±3.70 day and 1.53±0.03, respectively. Generation had non-significant (p>0.05) effect to all the respected traits. Parity and season of birth significantly (p<0.001) affected the ALS/doe. The litter size ranges 1.11 to 1.78, which increased linearly with the progressive parity of dam. Litter size (1.63±0.04) was found higher in summer, followed by winter (1.51±0.07) and rainy season (1.36±0.08). Estimated heritability for Bwt, AFS, AFK, AKI and ALS/doe were 0.46±0.12, 0.46±0.11, 0.49±0.11, 0.46±0.10 and 0.49±0.12, respectively. Though reproductive traits always have lower heritability estimates but all the estimates seem to have high magnitude. The range of estimated Breeding Value (EBV) of Bwt, AFS, AFK, AKI and ALS/doeversed over a wider context, which indicates there is scope for genetic improvement in next generation progeny except the Bwt trait. Altogether, the results of the investigated traits could be well used to select better candidates for producing next generation. Bang. J. Livs. Res. Vol. 29 (1&2), 2022: P. 21-33